Giggle Time - Establishing the Social Connection : a Program to Develop the Communication Skills of Children with Autism. - Sonders, Susan Aud (Jessica Kingsley Publishers, 2002)
Giggle Time is a step-by-step program for parents, teachers and other professionals to help develop the non-verbal, verbal and social reciprocity skills of children with autism. It describes in accessible detail how to communicate with children with autism and gives clear instructions on ''how to'' techniques for developing language skills. Specifically addressing developmental delays, Giggle Time helps to lay the necessary framework for future language growth by turning the actions the child initiates into interactions with meaning. This is a user-friendly guide, packed full of fun and child-